The Spiritual Level of Love on The Poetry “Wanita Cantik Sekali di Multazam” By A. Mustofa Bisri - Wachid B.S., Abdul; Kim Young Soo (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This article aims to reveal the concept of love and spiritual level according to A. Musthofa Bisri. In revealing this concept, this article uses the poem A Beautiful Woman in Multazam by A. Musthafa Bisri as the object of research. The selection of the poem